Molecular Approaches to Screen Bioactive Compounds from Endophytic Fungi - Vasundhara, M.; Kumar, Anil; Reddy, M. Sudhakara (Frontiers in Microbiology, 2016)
Endophytic fungi are capable of producing plant associated metabolites and their analogs with therapeutic value. In order to identify the potential endophytic isolates producing bioactive compounds, one need to screen all isolated endophytes, which may run into hundreds. Isolation of endophytic fungi is relatively a simple process; but screening of the isolated fungi for required metabolite production is a cumbersome process. Endophytic fungi producing plant associated metabolites may contain genes involved in the entire biosynthetic pathway(s). Therefore, ascertaining the presence of key enzymes of a particular biosynthetic pathway could serve as a molecular marker for screening of these endophytes to produce that metabolite. In absence of entire biosynthetic pathways in endophytic fungi, plant genes associated with that metabolic pathway could serve as markers. This review focuses on the impact of molecular approaches to screen the endophytic fungi for the production of bioactive compounds. An attempt has been made on screening of anticancer compounds like taxol (paclitaxel), podophyllotoxin and camptothecin using molecular markers. The advantages of molecular approaches over conventional methods to screen endophytic fungi and also identification of endophytic fungi are also discussed.